Cadmium, lead, tin, total mercury, and methylmercury in canned tuna commercialised in São Paulo, Brazil - Paiva, Esther Lima de (2017)
The objective of this work was to determine levels of inorganic contaminants in 30 samples of five commercial brands of canned tuna, acquired on the local market in Campinas, São Paulo, Brazil, in the year of 2015. Total mercury and methylmercury (MeHg+) were determined by atomic absorption with thermal decomposition and amalgamation; and cadmium, lead, and tin were determined by inductively coupled plasma optical emission spectrometry. Results indicated that 20% of the tuna samples surpassed limits determined by the Brazilian and European Commission legislation for cadmium; for lead, the maximum value found was 59 μg kg−1 and tin was not detected in any samples. The maximum values found for total Hg and MeHg+ were 261 and 258 μg kg−1, respectively. As from the results obtained, it was estimated that the consumption of four cans per week (540 g) of tuna canned in water could surpass the provisional tolerable monthly intake for MeHg+ by 100%.